2009
DOI: 10.1007/s00701-009-0214-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies of space-occupying intradural metastases of the cauda equina of nonneurogenic origin

Abstract: Surgical treatment of compressive intradural metastases of the cauda equina seems to be feasible with low operative risk and with the potential benefit of an immediate relief of pain and improvement in motor function and thus an increase in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Furthermore, it is unclear preoperatively which types of metastases will be amenable to complete resection. In some case reports, tumor resection was reported as en block [14,19,21,27,28], whereas others convey adherence of the tumor to neural elements precluding subtotal resection [7,10,18,20,22,23,26]. Our case was consistent with the latter-intimately associated with the intradural rootlets of the cauda equina.…”
Section: Surgical Considerationssupporting
confidence: 80%
“…Furthermore, it is unclear preoperatively which types of metastases will be amenable to complete resection. In some case reports, tumor resection was reported as en block [14,19,21,27,28], whereas others convey adherence of the tumor to neural elements precluding subtotal resection [7,10,18,20,22,23,26]. Our case was consistent with the latter-intimately associated with the intradural rootlets of the cauda equina.…”
Section: Surgical Considerationssupporting
confidence: 80%
“…Dagan et al (53) reported one case of cervical LM detected at follow-up imaging in one patient with no new spinerelated symptoms. Spine LMs were most frequently diagnosed at MRI T1-contrast scans with or without CSF cytologic analysis (66.7% and 25% cases, respectively), and confirmatory histopathological diagnosis was obtained only in 6 patients (7.3%) (23,26,30,56,62). At neuroimaging, most spine LMs were located in the lumbar-sacral (18.1%), thoracic-lumbar-sacral (18.1%), or lumbar (12.5%) regions, showing nodular (63.6%) or diffuse (36.4%) leptomeningeal enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment for these patients included intrathecal chemotherapy, 3 , 9 , 10 systemic chemotherapy, 3 , 10 , 13 , 15 spinal irradiation, 3 , 11 , 14 , 15 laminectomy, 13 , 16 19 high doses of dexamethasone, 11 , 14 and tyrosine kinase inhibitors. 12 The 35 patients undergoing a single medical intervention, excluding tyrosine kinase inhibitor treatment, survived an average of 3.19 months, 9 , 10 , 14 , 16 , 18 whereas the 5 patients who underwent tyrosine kinase inhibitor treatment or two or more interventions survived an average of 10.8 months. 3 , 12 , 13 , 15 , 19 Chemotherapy is the basic therapy for these patients.…”
Section: Discussionmentioning
confidence: 99%